PENGARUH KAMPANYE ZERO WASTE INDONESIA #TUKARBAJU TERHADAP SIKAP RAMAH LINGKUNGAN (SURVEI PADA FOLLOWERS INSTAGRAM @TUKARBAJU_) - Nabila Fatma Gaid (2022)
The phenomenon of environmental damage due to the fashion industry, namely the accumulation of textiles and fashion waste, is driven by the fast fashion industry. This industry is the second largest pollutant in the world, contributing a total of 10% and 20% of the world's wastewater, which is an environmentally damaging emission. This trend does not only impact the environment but also created consumptive attitudes in society. On behalf of this issue, Zero Waste Indonesia initiated a #TukarBaju campaign which is considered to be a solution for the textile and fashion waste accumulation in Indonesia. This quantitative research with positivism paradigm uses Ostergaard's campaign model theory intending to determine the impact of #Tukarbaju campaigns on environment-friendly attitudes carried out to a total of 100 Instagram followers of @tukarbaju_. Non-probability Sampling (Purposive Sampling) technique was used for the sampling. Sources for the research data include primary data and secondary data. Inferential statistic research analysis techniques with explanatory research types. Based on the results of a simple linear regression test, Zero Waste Indonesia's #TukarBaju (X) campaign has a positive impact on environment-friendly attitudes (Y). Following the former test, the results of the correlation test show a very strong level of correlation between variables at 0.862. The test result of the coefficient of determination is precisely 74.4%. The result of the T-test generates the existence of the impact of Zero Waste Indonesia's #TukarBaju campaign (X) on environment-friendly attitudes (Y). Thus, Zero Waste Indonesia's #TukarBaju campaign has a significant and positive effect on the environment-friendly attitudes of the Instagram followers of @tukarbaju_.